The Effect of Engage, Study, and Activate Method Towards Students’s Writing on Narrative Text - Nurbaeti, Enung; Rostiana, Heva (Universitas Mathla'ul Anwar Banten, 2019)
The research aims to know the effect of ESA method towards students’ writing on narrative text at the first grade students of MAN 3 Pandeglang in 2018/ 2019 academic year. The research paper employs non-equivalent control group design. It compares both of experimental group (O2-O1) and control group (O4-O3). In her research which is consisted of 172 that is took as sample 30 as Experimental Class and 30 as Control Class. In this research, the writers use the achievement test in calculating the need of data to the relevant problem, then, giving a treatment to the experimental class by using ESA method and using Lecturer method in control class. The writers use statistical computation in order to find out which hypothesis is accepted and which is rejected, (Ha) or (Ho). From research of data, it is found that tcount is higher than ttable in term of statistic, it could be seen that t-count ≥ t- table = 2,973 ≥2,002. It means that alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. Based on the finding, the writers concluded that ESA method has an influence in teaching writing on narrative text because it can more explore their imagination on written form.